Spatial distribution patterns and causal mechanisms of rainfall-induced clustered landslides: A case study from Southwestern Yunnan Province, China - Zongheng Xu; Yun Zeng; Yilong Li; Mei Yang (PLoS ONE, 2026)
Based on two major rainfall events that triggered clustered landslides in Changning, Baoshan, southwestern Yunnan Province, China, this study integrates multi-scale spatial analysis, systematic field investigations, and geomechanical characterization to examine the distribution patterns and rainfall-triggering mechanisms of clustered landslides. A total of 255 landslides were identified, exhibiting a belt-like distribution along the main river valleys with pronounced clustering at mid-to-high elevations and moderate slopes. High-incidence zones are concentrated at elevations of 1860 ~ 1900 m, slopes of 20° ~ 40°, and outcrops of gray-black thin-layered microcrystalline schist and gray-white quartz schist, with a strong orientation preference toward south- to southeast-facing slopes. Notably, landslide density on natural slopes located more than 500 m from roads is higher than in adjacent areas, indicating that the spatial pattern is primarily controlled by topography-lithology combinations rather than anthropogenic engineering disturbances. Microstructural analysis reveals pervasive schistosity, cleavage fractures, and clay-rich weathering bands, with weathering driving the evolution from dense to porous, loose structures, forming highly permeable, low-strength weak zones. Direct shear tests further show significantly reduced shear strength in shallow layers and weakened zones, which are highly sensitive to water content and external disturbances. Intense rainfall rapidly infiltrates, increases pore water pressure, and softens shallow layers, activating schistosity planes and inducing displacement, thereby promoting clustered and concentrated landslides. This study clarifies the spatial controls and coupled internal–external mechanisms of rainfall-induced landslides in metamorphic rock regions, providing essential scientific guidance for landslide hazard assessment and disaster mitigation planning in Yunnan’s mountainous watersheds.